Evaluation of variability in cell-free DNA extraction efficiency from plasma and urine and spike-in normalization - Fanny Sandberg; Nicholas Kueng; Carlo Rodolfo Largiadèr; Ursula Amstutz (Scientific Reports)
Abstract Cell-free DNA (cfDNA) is a promising new biomarker for clinical use in e.g. oncology and transplantation medicine. Urinary cfDNA is also gaining interest as a non-invasive biomarker. However, cfDNA extraction is not standardised, leading to a variety of different methods being used with varying efficiencies and size-specificities. In this study, we aimed to assess the variability in cfDNA extraction efficiency for multiple cfDNA extraction methods (QIAamp Circulating Nucleic Acid Kit, Zymo Quick-DNA Urine Kit, Q Sepharose protocol (Qseph)) using the artificial spike-in CEREBIS and compare the contribution of variable extraction efficiency to overall variability in cfDNA quantities determined using droplet digital PCR (ddPCR). We found reproducible extraction efficiencies specific for each method with 84.1% (± 8.17) in plasma, 58.7% (± 11.1) for Zymo, as well as 30.2% (± 13.2) for Qseph based on the 180 bp CEREBIS (Construct to Evaluate the Recovery Efficiency of cfDNA extraction and BISulphite modification) spike-in. Additionally, while the largest proportion of the technical variability was observed between extractions, it was almost negligible compared to the biological variability. Normalization of urinary cfDNA using creatinine in urine reduced the variability, whereas when normalizing for CEREBIS-based extraction efficiency this was not consistently observed. With overall relatively consistent extraction efficiencies within each cfDNA extraction method, normalization for extraction efficiency using CEREBIS thus did not show a clear benefit but might be considered for comparisons between extraction methods.